Interpretation of Local Wisdom in the Tula Bak Ritual as “the Other Home” among the Ile Boleng Community, Adonara, East Flores: Interpretasi Kearifan Lokal dalam Ritual Tula Bak Sebagai “Rumah Yang Lain” pada Masyarakat Ile Boleng, Adonara, Flores Timur - Ansel Bala Molan; Paulus Pati Lewar (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
This article aims to examine how the Ile Boleng people in Adonara, East Flores, East Nusa Tenggara, accord a central and special place to the “bak” (ferrocement tank) within their life. This treatment is revealed in the ritual stages of “Tula Bak” (the construction of “bak”). This study aims to describe and interpret it. The study, conducted using a qualitative approach, namely literature review, observation, and interviews in September 2024, resulted in one main finding that the ritual of “Tula Bak” parallel with the ritual of “Tula Uma Lango” (the contruction of dwelling house) in Lamaholot community. Through this parallelism, the “bak” acquires a sacred object and seems to possess spiritual power like a house. For the Lamaholot people, the house is not merely a place of residence; it is also a site of protection, a source of strength, and a wellspring of the spirit of life. Accordingly, this study is expected to contribute to society by helping preserve its culture and promoting a water-saving lifestyle amid the increasingly significant crisis of clean water scarcity.